Pengaruh Pijat Bayi Terhadap Ritme Menyusui: Analisis Durasi dan Frekuensi Pemberian ASI - Wulandari, Umianita Risca; Kumalasari, Dian (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
Breast milk is the optimal source of nutrition with a well-balanced composition for supporting a baby's growth and development. Therefore, it is essential that every baby receives adequate breast milk. The supply of breast milk can be affected by how often and how long breastfeeding sessions last. One method to increase both the frequency and duration of breastfeeding is baby massage. This study aimed to examine the impact of baby massage on the frequency and duration of breastfeeding in infants aged 0-6 months. A quasi-experimental research design with a pretest-posttest approach was employed. The population consisted of infants aged 0-6 months and mothers who were exclusively breastfeeding. A sample of 30 participants was selected using positive sampling. The results were analyzed using a paired sample t-test. The findings indicated an increase in the average breastfeeding frequency from 7 to 9 times per day and in the average breastfeeding duration from 15 to 19 minutes per session. Statistical analysis revealed a significant difference in both breastfeeding frequency (p=0.0001) and duration (p=0.0002) before and after baby massage.